Pengaruh Pendidikan Kewarganegaraan Terhadap Partisipasi Pemilih Pemula Pada Pemilihan Umum (Studi Kasus: Pemilu Gubernur Dan Wakil Gubernur Sumatera Utara Tahun 2018) - Napitupulu, Helen Novera (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
Simultaneous regional elections held in 2018 in 171 regions in Indonesia recorded voter reached 73.24% of the total permanent voters list (DPT) available. There has been a decrease in the level of community participation if compared to the 2017 elections which reached 74% (source: KPU Data)   Boosting the level of community participation in elections is not an easy thing. The right method and approach is needed especially to increase the participation of beginner voters. One method used is through citizenship education which contains material about democracy and human rights. This study aims to determine whether citizenship education for beginner voters can already be used as a basis in understanding and interpreting the general election and is there a significant effect of citizenship education on the increase in the participation of beginner voters in general elections.  From the research conducted on 200 adolescent voters in 3 senior high schools and 2 universities in Medan, it showed a significant effect of citizenship education on increasing the participation of beginner voters in general elections. This took a case study on the election of the Governor and Deputy Governor of North Sumatra in 2018, showing that there was a strong correlation between citizenship education and the level of participation of beginner voters. There is a coefficient of 0.659 and is a strong correlation because the value is more than 0.5. The correlation coefficient is positive, meaning that the better the citizenship education received by beginner voters, the higher the level of participation in the election.